Specific binding of solubilized adenylate cyclase to the erythrocyte cytoskeleton. - Sahyoun, N E (1981)
Concepts and criteria that have been developed for the study of the molecular organization of membrane-associated proteins are employed here to investigate the interaction of adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] with other membrane components. Detergent-solubilized adenylate cyclase can be shown to bind to erythrocyte-derived Triton X-100 shells containing cytoskeletal elements. This binding appears to be saturable with respect to adenylate cyclase concentration, and it is enhanced by the presence of divalent cations. Preactivation of the enzyme with 5'-guanylyl imidodiphosphate and isoproterenol, or with NaF, is a prerequisite for effective binding. Two exceptions to this general observation are noted: rat brain adenylate cyclase, which binds without prestimulation, and rat testicular cytosolic adenylate cyclase, which fails to bind under any of the conditions tried. The binding sites of the Triton X-100 shells are inactivated or released by treatment with various concentrations of trypsin or KCl. Moreover, exposure of the Triton X-100 shells to increasing temperatures results in a progressive loss of the adenylate cyclase binding capacity. On the basis of these and other findings, it is suggested that the adenylate cyclase complex possesses two principal domains that allow it to interact with both cytoskeletal elements and the lipid bilayer. The specific modulation of these interactions may be involved in the hormonal regulation of adenylate cyclase activity.